Impact of e-Government Services on Private Sector: An Empirical Assessment Model. - Hussain, Wasly; Ali, Al Soufi (2015)
Despite the large investments in the field of e-Government (e-Gov) around the world, little is known about the impact such investment. This is due to the lack of guidance evaluation, absence of appropriate tools to measure the impact of e-Gov on the private sector, as well as the lack of effective management to resolve or eliminate the barriers to e-Gov services that led to the failure or delay of many projects. This paper is primarily concerned in determining the impact of e-Gov services on the private sector. A combination of Modified Technology Acceptance Model (TAM), DeLone and McLean's of IS success will be utilized as a research model and e-Gov Economics Project (eGEP) framework to measure “Efficiency, Democracy & Effectiveness impact” for G2B services. The research result will help e-Gov decision makers to recognize the critical factors that are responsible for G2B success, specifically factors they need to pay attention to gain the highest return on their technology investment, hence enabling them to measure the impact for e-Gov on the private sector. The paper has also demonstrated the usefulness of Structural Equation Modeling (SEM) in analysis of small data sets and in exploratory research.